Support from the Internet for Individuals with Mental Disorders: Advantages and Disadvantages of e-Mental Health Service Delivery - Moock, Jörn (Frontiers in Public Health, 2014)
Mental disorders are common in almost all industrialized countries and many emerging economies. While several trials have shown that effective treatments exist for mental disorders, such as pharmacotherapy, psychological interventions, and self-help programs, the treatment gap in mental health care remains pervasive. Unrestricted access to adequate medical care for people with mental disorders will be one of the pressing public mental health tasks in the near future. In addition, scarcity of financial resources across the public mental health sector is a powerful argument for investigating innovative alternatives of delivering mental health care. Thus, one challenge that arises in modern mental health care is the development of innovative treatment concepts. One possibility for improving mental health care services is to deliver them via the Internet. Online-based mental health services have the potential to address the unmet need for mental health care.